2022
DOI: 10.3390/plants11050685
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA-Regulated SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL) Gene Expression and Cytokinin Accumulation Distinguish Early-Developing Male and Female Inflorescences in Oil Palm (Elaeis guineensis)

Abstract: Sexual differentiation of inflorescences and flowers is important for reproduction and affects crop plant productivity. We report here on a molecular study of the process of sexual differentiation in the immature inflorescence of oil palm (Elaeis guineensis). This species is monoecious and exhibits gender diphasy, producing male and female inflorescences separately on the same plant in alternation. Three main approaches were used: small RNA-seq to characterise and study the expression of miRNA genes; RNA-seq t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The gene squamosa promoter-binding-like protein_6 (SPL6) (LOC103724287) in K. elegans is homologous to SPL8 in Arabidopsis thaliana, involved in anther development and male fertility (30). Additionally, the sex-linked transcription factor phytochrome interacting factor-like 15 (PIL) (LOC103697220) in K. elegans is similar to PIL family factors that interact with SPLs (31) and is orthologous to the oil palm LOC105059744 gene that displays sex-dependent expression (32). All the sexlinked genes mentioned have homologs positioned in the 43 and 46.1Mb region of the E. guineensis chromosome 10, except the LOG3 gene located in the chromosome 12 (Table 1).…”
Section: A Common Sex-linked Region In P Dactylifera and K Elegans Of...mentioning
confidence: 99%
“…The gene squamosa promoter-binding-like protein_6 (SPL6) (LOC103724287) in K. elegans is homologous to SPL8 in Arabidopsis thaliana, involved in anther development and male fertility (30). Additionally, the sex-linked transcription factor phytochrome interacting factor-like 15 (PIL) (LOC103697220) in K. elegans is similar to PIL family factors that interact with SPLs (31) and is orthologous to the oil palm LOC105059744 gene that displays sex-dependent expression (32). All the sexlinked genes mentioned have homologs positioned in the 43 and 46.1Mb region of the E. guineensis chromosome 10, except the LOG3 gene located in the chromosome 12 (Table 1).…”
Section: A Common Sex-linked Region In P Dactylifera and K Elegans Of...mentioning
confidence: 99%
“…CTK also has an important regulatory effect on grain storage capacity (library strength) (Chen et al, 2019). During development of the floral organ meristem, an increase in CTK concentration or an increase in CTK signaling pathway activity promotes cell division and differentiation of the floral organ meristem, thereby increasing the number of reproductive organs (Tregear et al, 2022). A reduction in the activity of CTK oxidase CKX can increase the CTK content and increase the storage capacity of the grain.…”
Section: Ctk Regulation Of Source‐sink Relationship and Mechanism Of ...mentioning
confidence: 99%
“…Despite many advancements in the prediction and characterization of miRNAs in plants, there are only a few studies where researchers report the identification and characterization of miRNAs in oil palm, either under abiotic stress conditions or not. Currently, there are 10 published studies reporting miRNAs identification and characterization in oil palm [15,30,[56][57][58][59][60][61][62][63]. Considering the great economic importance of oil palm, the number of miRNA studies reported on this oilseed crop is relatively low (Table 1).…”
Section: Mirnas In Oil Palm (Elaeis Spp)mentioning
confidence: 99%
“…They found 37 fatty acid synthesis-related genes as putative miRNA-target genes and indicated that 22 conserved miRNAs and 14 new ones might be involved in fatty acid metabolism pathways. Tregear et al [63] reported finding 30 previously unreported oil palm miRNA genes in a molecular study of the process of sexual differentiation in the immature inflorescence of oil palm.…”
Section: Mirnas In Oil Palm (Elaeis Spp)mentioning
confidence: 99%